2009
DOI: 10.1016/j.nbt.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Growth and profitability in small privately held biotech firms: preliminary findings

Abstract: This paper reports on preliminary findings on a study of the relationship of growth and profitability among small privately held Finnish Life Science firms. Previous research results concerning growth and profitability are mixed, ranging from strongly positive to a negative relationship. The conventional wisdom states that growth is a prerequisite for profitability. Our results suggest that the reverse is the case. A high profitability-low growth biotech firm is more probably to make the transition to high pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
3
18
0
1
Order By: Relevance
“…Hence, while firms differ substantially cross-sectionally, changes in profitability and sales growth lead to important changes in the outcome variables. This highlights the theoretical notion that profitability and growth differences among firms tend to be fairly stable over time, but that a transition from a non-profitable to a profitable firm is relatively rare (Brännback et al, 2009;Coad, 2010). This highlights the importance of controlling for the potential of unobserved differences in studies of firm growth.…”
Section: Robustness Testsmentioning
confidence: 78%
See 2 more Smart Citations
“…Hence, while firms differ substantially cross-sectionally, changes in profitability and sales growth lead to important changes in the outcome variables. This highlights the theoretical notion that profitability and growth differences among firms tend to be fairly stable over time, but that a transition from a non-profitable to a profitable firm is relatively rare (Brännback et al, 2009;Coad, 2010). This highlights the importance of controlling for the potential of unobserved differences in studies of firm growth.…”
Section: Robustness Testsmentioning
confidence: 78%
“…Their approach involved categorizing firms at the beginning of the observation period in terms of growth and profitability achieved and then examining the probability of individual firms moving from one category to another. This approach was subsequently espoused by Brännback et al (2009) who analyzed 336 Finnish life science firms. They find profitability to be positively associated with sales growth, but not the reverse.…”
Section: The Empirical Puzzle Of Growth Profitability and Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews in the field, however, agree that selfreported measures correspond well with actual measures (Shepherd and Wiklund 2009). In addition, Davidsson, Steffens, and Fitzsimmons (2009) and Brännback et al (2009) showed that early profit actually drives subsequent profitable growth.…”
Section: Business Planning and Nascent Entrepreneursmentioning
confidence: 99%
“…The literature on biotechnology startups is rich both from an academic as well as business-oriented standpoint. A few general books can be quoted (Shimasaki 2014, Binder 2008, Hughes 2011) and academic work is numerous even if again a few articles are worth being mentioned (Audretsch 2001;Bradford 2003;Brännback et al 2009;Zahn and Patel 2005;Zucker et al 1998). A recent publication by Tzabbar & Margolis (2017) exemplifies some unique features of the roles of founders.…”
Section: Introductionmentioning
confidence: 99%